The positive psychology of personal transformation leveraging resilience for life change - Garbarino, James; SpringerLink (Online service). (New York Springer, 2011)
Given the current climate of economic and environmental uncertainty, it is all too easy for individuals to feel hopeless about their lives and indifferent to the problems of others. But according to leading psychologist, James Garbarino, this is the peak time for people to enhance their optimism, empathy, and emotional responsiveness. In his important new book, The Positive Psychology of Personal Transformation, Dr. Garbarino reveals the social basis for moral development in adversity, and the mental and physical benefits of psychological and spiritual growth. Drawing widely on his years as a healing professional and own experience of personal crisis as well as on decades of resilience and happiness literature, the author traces the evolution of the moral sense that affects all human relationships, including the one with the Earth itself. In these compelling pages, Dr. Garbarino: Examines how humans deep bonds with dogs can model positive human relationships. Compares the risks and benefits of the oblivious versus the self-aware life. Analyzes the role of trauma in heightening our sense of the meaning of life and defines the experience of transformational grace in adversity. Explains current manifestations of narcissism and the need for the positive death of the self. Asserts that every person is capable of living an extraordinary life. A book with vast significance across the healing disciplines, The Positive Psychology of Personal Transformation should be read, savored, and practiced by researchers, practitioners, and scientists in clinical child, school, and developmental psychology; social work; educational and community psychology; sociology; and public health.
Preface -- Acknowledgments -- Walking With Hope and Dharma: Are Dogs Enlightened? Are Humans?- The Costs and Benefits of Obliviousness: Growing Up in the 1950s -- Ten Bad Things That Almost Happened, And Many More That Did: Getting to the Other Side of Trauma -- What is the Opposite of Trauma? The Power of Transformational Grace -- Can There Ever Be Enough Me? Narcissism And the Positive Death of Self -- What Does It Mean to Live an Extraordinary Life?- References.
Electronic reproduction.
Keywords: Positive psychology; Electronic books